2011
DOI: 10.1002/sia.3825
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of Ni–Co–P/nano‐sized Si3N4 electroless composite coatings

Abstract: Ni-Co-P/nano-sized Si 3 N 4 composite coating was successfully fabricated on aluminum alloys by electroless plating in this work. The surface and cross-sectional morphologies, composition, microstructure, microhardness, friction and wear behavior of deposits were investigated with SEM, EDS, XRD, Vickers hardness and high-speed reciprocating friction, respectively. It was found that a Ni-Co-P/nano-sized Si 3 N 4 composite coating on aluminum alloy substrate is uniform and compact. The existence of nano-sized Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…To achieve a better wear resistance, it is necessary to ensure (i) a high number density of nanoparticles, (ii) uniform distribution, (iii) better integrity between the nanoparticles and the Ni-P matrix, and (iv) heat treatment to impart a high hardness and to present an incompatible surface for the counterface material during wear. The tribological performance of EL Ni-P nanocomposite coatings incorporated with CNTs/ MWCNTs [6][7][8]12], Si 3 N 4 [23], SiO 2 [42], Al 2 O 3 [25], HNT [18], WS 2 [20], and WC [15] nanoparticles confirms the above attributes.…”
Section: Tribological Characteristicssupporting
confidence: 81%
See 3 more Smart Citations
“…To achieve a better wear resistance, it is necessary to ensure (i) a high number density of nanoparticles, (ii) uniform distribution, (iii) better integrity between the nanoparticles and the Ni-P matrix, and (iv) heat treatment to impart a high hardness and to present an incompatible surface for the counterface material during wear. The tribological performance of EL Ni-P nanocomposite coatings incorporated with CNTs/ MWCNTs [6][7][8]12], Si 3 N 4 [23], SiO 2 [42], Al 2 O 3 [25], HNT [18], WS 2 [20], and WC [15] nanoparticles confirms the above attributes.…”
Section: Tribological Characteristicssupporting
confidence: 81%
“…If nanoparticles could act as nucleation sites, then one would expect an increase in the rate of deposition. Hu et al [23] have reported that addition of Si 3 N 4 nanoparticles to EL Ni-Co alloy plating bath has increased the number of catalytic active sites and increased the rate of deposition from 4.2 to 5.6 mm. Addition of TiN nanoparticles, however, has caused a decrease in the deposition rate from 11 to 5 mm [21].…”
Section: Alternate Methods Of Preparation Of El Ni-p Nanocomposite Comentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the Ni-P coatings prepared by electroless plating have some outstanding mechanical and chemical properties, such as good corrosion resistance, wear-resistance and high microhardness etc. 4,5 . On the other hand, the electroless plating has the advantage of its ability to coat interior surfaces of pipes, valves, and other parts.…”
Section: Introductionmentioning
confidence: 99%